Creating Service with Thai Hospitality: What Does Service Providers Highlight for Hotel Service in Thailand? - PIUCHAN, Manisa (Journal of Environmental Management and Tourism, 2023)
This study aims to explore service components in Thai hospitality which are prepared and provided by the service providers in order to creating impressive service in the hotel sector in Thailand and are presented to tourists as the core value of Thai hospitality. The mixed methods were employed using interview and questionnaire survey. Samples were the frontline hotel service providers to obtain valuable opinions and various perspectives regarding service and its practice in hotel. Data were collected from 11 interviews and 320 questionnaires. The interview thematic analysis and exploratory factor analysis (EFA) were the main analysis of the research. Results showed seven service components which could be the core value in Thai hospitality included professional traits, the senses of service (intangibility), workplace culture and skills, service tangibility, Thai service providers, Thai nurture and practices and hotel ambience. The service components founded in Thailand can support the strong bond between Thai culture, service offerings and service providers. These also can help the hotels to gain more advantage in their businesses and lift up the competitiveness of Thai hospitality in hotel service.